Membangun Self Love pada Remaja melalui Psikoedukasi: Building Self Love in Teenagers with Psychoeducation - Mursalim, Alifiah Hidayati; Eryandra, Alvin (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Forming an image of oneself, roles, interests, values, beliefs, and physical changes begins when entering adolescence. This generally makes teenagers vulnerable to low self-esteem due to a lack of self-love. To anticipate this, an effort is needed to build understanding among teenagers regarding self-love so that they can recognize and respect themselves through psychoeducation activities. This psychoeducation activity is carried out using three stages, namely the planning, implementation, and evaluation stages. The planning stage is carried out by surveying the subject's condition and location of the activity site and coordinating with related parties. The implementation stage of psychoeducation activities involves delivering material and cultivating understanding related to self-love. The evaluation stage is done by looking at the pre-test and post-test results. The subjects of this psychoeducational activity were 28 students at SMPN 2 Lemahabang, Cirebon Regency, aged 13-15 years. The instrument was a questionnaire, and psychoeducation activities were implemented for one month. The results of psychoeducation activities show that there is an increase in the understanding of teenagers at SMPN 2 Lemahabang regarding self-love.